PENCITRAAN PEREMPUAN DALAM NOVEL AYAT- AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Fauziah Khairani Lubis (BAHAS, 2016)
The novel entitled Ayat-Ayat Cinta written by Habiburrahman El Shirazy is considered phenomenal because it brings forward the religious theme. The novel describes the life of women with Islam values as its foundation. This has impressed the society since they feel bored with the radical feminism themes bringing too much emphasis on the freedom of sex and lusts that appear in the literature so often. This analysis is aimed at describing the images of women in the novel. To analyze the images of women, the theory of psychology of literature is applied. The finding of this research shows that the images of women in the novel are beautiful, motherly, independent, heroic, wise, smart, loving, revengeful, slanderous and impatient to face problems. AAC is considered as the religious novel that conveys Islam point of view about women both implicitly and explicitly. This is shown from the activities of the women in carrying out the Islam values which are based on the verses of Al Qur’an and Hadits. The characters in AAC show the attitude of being patient and being submissive to God, putting effort to get something, praying to God, keeping the dignity of one’s husband, putting effort to gain knowledge, doing sunnah. Keywords: the images of women, religious, theory of psychology, Islam values